Cooperative optimization algorithm for wind turbine airfoil design and numerical validation of blade aerodynamic and flutter performance - Su, Hongjie; Ma, Jianlong; Wang, Jianwen; Gao, Zhiying; Li, Qiuyan; Pan, Wenli; Yang, Long (Energy conversion and management, 2025)
•Introduced a novel airfoil optimization method.•Developed algorithms improving aerodynamic and flutter performance.•CFD simulations showed a 5.07% increase in aerodynamic efficiency.•Structural analysis indicated a 24% higher flutter boundary. Wind turbines hold substantial promise for harnessing wind energy, yet the blades endure severe unsteady aerodynamic loads due to prolonged operation in complex environments. These loads adversely affect both aerodynamic and structural performance. The aerodynamic and structural properties of airfoils are critical determinants of overall blade effectiveness. To enhance aerodynamic and anti-flutter performance, this study proposed an optimization approach for wind turbine airfoils using a Hybrid Bi-Directional Cooperative Constrained Multi-Objective Evolutionary Algorithm (HBC-COMEA). Airfoil geometries were parameterized via Non-Uniform Rational B-Splines (NURBS), and optimization was performed with the lift-to-drag ratio and polar moment of inertia as the objective functions, subject to constraints on maximum airfoil thickness. The NREL 5 MW wind turbine blade served as the study model, with optimizations performed on airfoils located at different blade sections, including NACA64618 (18 % relative thickness), DU93-W-210 (21 % relative thickness), and DU91-W2-250 (25 % relative thickness). The results demonstrated improvements in both aerodynamic performance and polar moment of inertia. Replacing the original airfoils with the optimized ones led to a 5.07 % increase in blade torque at the rated wind speed. Additionally, flutter analysis indicated a 24 % enhancement in the flutter boundary and a significant reduction in the torsional vibration amplitude of the blade. These findings validate that the proposed optimization method markedly improves overall blade performance, offering a promising approach for optimizing airfoils in large wind turbine blades.